(untitled) (Revista de Investigaciones Universidad del Quindío, 2009)
The composition, seasonality and habitat of the fish from the Cristales creek, tertiary tributary of the La Vieja river, upper Cauca, Colombia, was studied from June 2004 to January 2005. Sixteen species of four orders and five families were captured; the captures were made with standard methods through 14 stations distributed in the creek. Brycon henni species were constant to both climatic periods and in the low area of the creek. Poecilia caucana were the species with higher occurrence percentage for both periods and the only constant species for the high area. Apteronotus sp., Argopleura magdalenensis, Bryconamericus caucanus, Chaetostoma fischeri, Characidium caucanum, Imparfinis nemacheir, Lasiancistrus caucanus, Rhamdia quelen, and Roeboides dayi were accidental and they were captured when we were very close to the outlet creek, and these species were observed in the half and low parts of the creek. Physicochemical and habitat characteristics were evaluated. Many species were associated to microhabitats with abundant riverside vegetation and aquatic macrophyties.